2004
DOI: 10.2478/bf02482725
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of the hydration of short-chain poly(oxyethylene)s C 1EnC 1 (n=1−4)

Abstract: The hypothesis that the degree of hydration of poly(oxyethylene) (POE) in aqueous solution depends on the mole ratio of water molecules to ether oxygen atoms in the molecule has been verified by studying the isotropic Raman spectra in the O-H stretching region for four short-chain POEs (C 1 E n C 1 with n = 1−4). Excellent coincidence of the O−H stretching Raman band for all four POEs studied in the range of mole ratio H 2 O/O ether from 25 to 0.6 was observed, thus confirming the assumption stated above. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…After Giemsa staining and comparison the wheat T. aestivum cv. Chinese Spring and rye chromosomes it was established that, the rye chromosome pair 2R is missing and was substituted with 2D chromosome of wheat (11). Analysis of nucleolar activity in triticale cultivar 171 (AABBRR), showed only four major silver-positive NORs and four signals in interphase cells after in situ hybridisation of wheat chromosomes 1B and 6B (Tables 1, 2), supporting previous observations of (6, 7, 20, In contrast mutant form of MT47 and K1 (in this issue) showed six well-defi ned silver-positive NORs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After Giemsa staining and comparison the wheat T. aestivum cv. Chinese Spring and rye chromosomes it was established that, the rye chromosome pair 2R is missing and was substituted with 2D chromosome of wheat (11). Analysis of nucleolar activity in triticale cultivar 171 (AABBRR), showed only four major silver-positive NORs and four signals in interphase cells after in situ hybridisation of wheat chromosomes 1B and 6B (Tables 1, 2), supporting previous observations of (6, 7, 20, In contrast mutant form of MT47 and K1 (in this issue) showed six well-defi ned silver-positive NORs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the study by Blandamer et al, a large number of experimental and theoretical studies have been performed to elucidate the relationship between the solubility property and the conformation of POE. A Raman spectroscopic study indicated that the spectra of POE in aqueous solutions are similar to that of the crystal rather than that of the pure liquid, suggesting that POE in aqueous solution prefers to form a helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the shortest POE, 1,2-dimetoxyethane (DME) (CH 3 O–CH 2 –CH 2 –OCH 3 ), is worth considering as a model molecule because the conformation of DME completely corresponds to the conformational unit of POE. Indeed, there have been a large number of studies using DME as a model molecule. ,, The conformers of DME can be quantitatively analyzed by vibrational spectroscopy. A Raman study by Matsuura et al confirmed that the fraction of the tgt conformer of DME increases with increasing water concentration, while the fractions of the ttt and tgg ′ conformers decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The parallel and the perpendicular components of the scattered radiation were used in order to calculate the isotropic spectra. 4 'iso =' (2) To increase the accuracy in following analysis every spectrum is an average of 1 000 scans. …”
Section: Methodsmentioning
confidence: 99%